Quantifying the ability of magnetohydrodynamic models to reproduce observed Birkeland current and auroral electrojet magnitudes - James, Tre’Shunda; Lopez, Ramon E.; Glocer, Alex (Frontiers in Astronomy and Space Sciences, 2023)
Although global magnetohydrodynamic (MHD) models have increased in sophistication and are now at the forefront of modeling Space Weather, there is still no clear understanding of how well these models replicate the observed ionospheric current systems. Without a full understanding and treatment of the ionospheric current systems, global models will have significant shortcomings that will limit their use. In this study we focus on reproducing observed seasonal interhemispheric asymmetry in ionospheric currents using the Space Weather Modeling Framework (SWMF). We find that SWMF does reproduce the linear relationship between the electrojets and the FACs, despite the underestimation of the currents' magnitudes. Quantitatively, we find that at best SWMF is only capturing approximately 60% of the observed current. We also investigate how varying F10.7 effects the ionospheric potential and currents during the summer and winter. We find that simulations ran with higher F10.7 result in lower ionospheric potentials. Additionally, we find that the models do not always replicate the expected behavior of the currents with varying F10.7. This work points to a needed improvement in ionospheric conductance models.